2020
DOI: 10.5253/arde.v107i3.a7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Egg Size of Black-Tailed Godwits

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…1). In 111 of 151 cases, we observed an egg-laying phase denoted by 20 or more min of shading for 1-3 days, immediately followed by an incubation phase denoted by long shaded periods lasting 1-10 h. This pattern is consistent with known godwit nesting behaviour, as most godwits lay 3-4 eggs (Haverschmidt 1963, Verhoeven et al 2019a, both females and males spend short periods sitting on the nest during the egg-laying phase, and incubation begins after the penultimate or ultimate egg is laid (Haverschmidt 1963). In the remaining 40 cases, we did not observe an egg-laying phase but did observe a clear incubation phase.…”
Section: Inferring Incubation Duration and Hatching Success From Geolsupporting
confidence: 79%
“…1). In 111 of 151 cases, we observed an egg-laying phase denoted by 20 or more min of shading for 1-3 days, immediately followed by an incubation phase denoted by long shaded periods lasting 1-10 h. This pattern is consistent with known godwit nesting behaviour, as most godwits lay 3-4 eggs (Haverschmidt 1963, Verhoeven et al 2019a, both females and males spend short periods sitting on the nest during the egg-laying phase, and incubation begins after the penultimate or ultimate egg is laid (Haverschmidt 1963). In the remaining 40 cases, we did not observe an egg-laying phase but did observe a clear incubation phase.…”
Section: Inferring Incubation Duration and Hatching Success From Geolsupporting
confidence: 79%
“…However, these phenological studies are inter-specific comparisons focusing either on population means or 'first individual' observations, rather than examining individual-level variation using repeated measures. Similar to our study, Verhoeven et al (2019) found no influence of winter region on intra-individual variation in migration timing. High intra-individual variation has also been reported for some long-distance migrants (e.g.…”
Section: Influence Of Migration Distance On Individual Variationsupporting
confidence: 91%
“…Inter-individual variation for most behaviours examined was high. High inter-individual variation might suggest that selective pressure on these behaviours is low for this species (Verhoeven et al, 2019).…”
Section: Accepted Articlementioning
confidence: 97%
“…Several studies of oviparous organisms have observed age-dependent variation in egg size, with some studies finding a positive relationship (Cooch et al, 1992;Flint & Sedinger, 1992;Robertson et al, 1994;Warner et al, 2016;Verhoeven et al, 2020) and others observing a negative relationship (Reid, 1988;Potti, 1993;Ito, 1997). However, several of these studies failed to account for selective disappearance (e.g., Cooch et al, 1992;Flint & Sedinger, 1992;Potti, 1993) and thus complicate the interpretation of individual-vs. population-level effects.…”
Section: Discussion (1375 Words)mentioning
confidence: 99%
“…We followed common statistical approaches to investigate senescence in birds (e.g., Bouwhuis et al, 2009Bouwhuis et al, , 2010Schroeder et al, 2012;Herborn et al, 2016;Graham et al, 2019;Dingemanse et al, 2020) (Dittmann & Hötker, 2001;Skrade & Dinsmore, 2013;Kwon et al, 2018;Kubelka et al, 2020;Verhoeven et al, 2020). We standardized lay date according to year so that breeding season phenology was comparable across years.…”
Section: Data Collectionmentioning
confidence: 99%